Coagulation Factor IIIa (f3a) Knockdown in Zebrafish Leads to Defective Angiogenesis and Mild Bleeding Phenotype - Subramaniam, Saravanan; Liu, Jiandong; Fletcher, Craig; Ramchandran, Ramani; Weiler, Hartmut (Frontiers in Cell and Developmental Biology, 2022)
Tissue factor (TF) is crucial for embryogenesis, as mice lacking TF are embryonically lethal (E10.5). This lethality Tissue factor (TF) is crucial for embryogenesis, as mice lacking TF are embryonically lethal (E10.5). This lethality may be attributed to defects in vascular development and circulatory failure, suggesting additional roles for TF in embryonic development beyond coagulation. In this study, we characterized the role of one of the TF paralogs (f3a) using a zebrafish model. The expression of f3a during embryonic developmental stages was determined by RT-PCR. Spatiotemporal expression pattern of f3a revealed (high expression from 28 to 36 hpf) the role of in the development of the yolk sac, circulation, and fins. Morpholinos (MO), an antisense-based oligonucleotide strategy, was used to knockdown f3a and examined for defects in morphological appearance, bleeding, and vascular patterning. f3a MO-injected embryos showed morphological abnormalities, including shorter body lengths and crooked tails. O-dianisidine staining showed f3a MO-injected embryos exhibited bleeding in the trunk (5.44%) and head (9.52%) regions. Imaging of endothelial-specific transgenic lines (flk1:egfp-NLS/kdrl:mCherry-CAAX) showed a 3-fold decreased caudal vein plexus (CVP) in f3a morphants versus controls at 48 hpf, suggesting a potential role for f3a in angiogenesis. These findings confirm that f3a is essential for angiogenesis, in addition to its involvement in hemostasis.